Robust risk‐averse unit commitment with solar PV systems. Issue 15 (5th November 2020) - Raygani, Saeid Veysi; Forbes, Michael; Martin, Daniel
Abstract : A challenge for energy market operators (EMOs) is to render a cost‐effective generation schedule, known as unit commitment (UC), for the power system with intermittent renewable power generations. Consolidating the risk management concept and robustness into the UC not only helps EMO to maintain the secure operation of power systems but also informs the EMO about the tail‐risk cost. Based on this motivation, the authors have proposed a model for UC with worst‐case conditional value‐at‐risk (UC‐WCVaR) with intermittent solar generations and loads. Unlike intractable risk‐averse stochastic UC models, this model minimises the worst‐case CVaR of the dispatch cost over an ambiguity set of the probability distributions. This robust tractable model relies on the historical data that can partially characterise the underlying probability distributions of solar photovoltaic (PV) systems and loads. They solved this model by its equivalent tractable robust counterpart using linear decision rules. The tests conducted on the IEEE 118‐bus test system demonstrate that: (i) UC‐WCVaR solution matches the results derived from normally distributed solar samples; (ii) the UC‐WCVaR is less conservative than the classic robust unit commitment. Also, the computation time is directly proportional to the number of uncertain resources and inversely proportional to the number of stages.